The wheels on the bus - Cooke, Andy (Lutherville,MD. : Flying Frog, 1999)
An illustrated version of the traditional song.
"Beginnings, age 2+"--Cover.
2.8
K-3
Keywords: Children's songs -- Texts; Songs; Songs